2020
DOI: 10.1016/j.heliyon.2020.e03970
|View full text |Cite
|
Sign up to set email alerts
|

A multi-approach assessment of land use effects on groundwater quality in a karstic aquifer

Abstract: Groundwater represents almost half of the drinking water worldwide and more than one third of water used for irrigation. Agro-industrial activities affect water resources in several manners; one of the most important is leaching of agrochemical residues. This research identifies the major contributors of changes in groundwater quality comparing two contrasting land uses in a karstic area of the Yucatan peninsula as case study. Using a multiple approach, we assess the impact of land use with physicochemical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
12
0
7
Order By: Relevance
“…In Dobrogea, another important karst area in Romania, Moldovan et al reported excellent to good water quality and, for a couple of sources, the presence of possible health risk due to the high content of NO 3 − , Cd and Cr [47]. Nitrate pollution is one of the most important causes of groundwater pollution, being the main reason for poor groundwater quality in a karst region in Central America [54], while TDS is reported to be the reason for the poor quality of a groundwater in Tefenni, Turkey [55]. Water with low quality is mainly characterized by high values of NO 3 − , Cl − , SO 4 2− , Ca, Mg and Na, due to natural interactions such as weathering of rocks and evaporation processes, or to anthropogenic influences, especially pollution with organic materials subject to underground nitrification processes.…”
Section: Groundwater Quality Index (Gwqi)mentioning
confidence: 99%
“…In Dobrogea, another important karst area in Romania, Moldovan et al reported excellent to good water quality and, for a couple of sources, the presence of possible health risk due to the high content of NO 3 − , Cd and Cr [47]. Nitrate pollution is one of the most important causes of groundwater pollution, being the main reason for poor groundwater quality in a karst region in Central America [54], while TDS is reported to be the reason for the poor quality of a groundwater in Tefenni, Turkey [55]. Water with low quality is mainly characterized by high values of NO 3 − , Cl − , SO 4 2− , Ca, Mg and Na, due to natural interactions such as weathering of rocks and evaporation processes, or to anthropogenic influences, especially pollution with organic materials subject to underground nitrification processes.…”
Section: Groundwater Quality Index (Gwqi)mentioning
confidence: 99%
“…IW has a more de ned chemical composition, the carbonate minerals are around equilibrium, but it also acquired characteristics of in ltrating water that has passed through the soil, such as acidic pH, reductive conditions and organic matter decomposition (Craft et al 1991). Similar electrical conductivity in GW and IW is assumed as comparable amount of dissolved solids was found in those compartments; the former due to the water-rock interaction (Smith et al 2020), the latter due to the solubilisation of several substances around the rhizosphere (Raghavendra et al 2016). In summary, this marsh is a good site to evaluate in detail the water in ltration process and the chemical changes that occur in the water during this process.…”
Section: Discussionmentioning
confidence: 99%
“…32 ISSN 2549-7197 (cetak), ISSN 2549-564X (online) JMEL, Volume 5 Nomor 1, 2021 Smith et al (2020) stated that residential areas could be a nitrate contributor to the environment associated with septic tank leakage with higher concentrations. So it is necessary to control and monitor good sanitation channels in waste disposal so that it does not become a source of pollution.…”
Section: Correlation Of Landuse and Nitrate Concentration In Groundwatermentioning
confidence: 99%